miR444a has multiple functions in the rice nitrate‐signaling pathway - Yan, Yongsheng; Wang, Huacai; Hamera, Sadia; Chen, Xiaoying; Fang, Rongxiang (The Plant journal : for cell and molecular biology, 2014)
Nitrate (NO3−) is a key signaling molecule in plant metabolism and development, in addition to its role as a nutrient. It has been shown previously in Arabidopsis that ANR1, a MADS‐box transcription factor, is a major component in the NO3−‐signaling pathway that triggers lateral root growth and that miR444, which is specific to monocots, targets four genes that are homologous to ANR1 in rice. Here, we show that miR444a plays multiple roles in the rice NO3−‐signaling pathway – not only in root development, but also involving nitrate accumulation and even Pᵢ‐starvation responses. miR444a overexpression resulted in reduced rice lateral root elongation, but promoted rice primary and adventitious root growth, in a nitrate‐dependent manner. In addition, overexpression of miR444a improved nitrate accumulation and expression of nitrate transporter genes under high nitrate concentration conditions, but reduced the remobilization of nitrate from old leaves to young leaves thus affecting the plant's ability to adapt to nitrogen‐limitating conditions. Intriguingly, we found that Pᵢ starvation strongly induced miR444 accumulation in rice roots and that overexpression of miR444a altered Pᵢ‐starvation‐induced root architecture and enhanced Pᵢ accumulation and expression of three Pᵢ transporter genes. We further provide evidence that miR444a is involved in the interaction between the NO3−‐signaling and Pᵢ‐signaling pathways in rice. Taken together, our observations demonstrated that miR444a plays multiple roles in the rice NO3−‐signaling pathway in nitrate‐dependent root growth, nitrate accumulation and phosphate‐starvation responses.